2022
DOI: 10.1097/qai.0000000000002893
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Heroin and HIV on Gut Integrity and Immune Activation

Abstract: Background: Altered gut integrity is central to HIV-related immune activation. Opioids may promote similar changes in gut permeability and/or increase systemic inflammation, potentially augmenting processes already occurring in people with HIV (PWH). Setting: Urban hospital systems in Cleveland, Ohio, and surrounding communities. Methods: This is a prospectively enrolled, cross-sectional study including people with and without HIV using heroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
3
4
0
Order By: Relevance
“…Our results aligned with previous reports examining the state of inflammation in virally suppressed PWH with IDU and OUD (9,28,32,33), showing increased expression of IL-6 (opioid use) (32), IL-8, sTNFR-II (methadone use) (28), and LBP, hsCRP, sTNFR-I, sTNFR-II, sCD14, sCD163 (heroin use) (28,32,33). In our study, plasma biomarkers were selected based on their reported association with inflammation (sTNFR-II, sTNFR-I, sCD25, TNFa, IL-6, IL-8, IL-1a, IL-1b, IL17A (Th17), IL-22 (Th17)) (34), cardiovascular disease (ICAM-I, VCAM-I, hsCRP), co-morbidities (IL-6, VCAM-I, ICAM-I, sTNFR-II, and sTNFR-I), monocyte activation and microbial translocation (sCD14, sCD163, iFABP, D-dimer, LBP) (32), HIV disease progression (MCP1/CCL2, sCD14) and mortality (sCD14) in the context of HIV.…”
Section: Discussionsupporting
confidence: 93%
“…Our results aligned with previous reports examining the state of inflammation in virally suppressed PWH with IDU and OUD (9,28,32,33), showing increased expression of IL-6 (opioid use) (32), IL-8, sTNFR-II (methadone use) (28), and LBP, hsCRP, sTNFR-I, sTNFR-II, sCD14, sCD163 (heroin use) (28,32,33). In our study, plasma biomarkers were selected based on their reported association with inflammation (sTNFR-II, sTNFR-I, sCD25, TNFa, IL-6, IL-8, IL-1a, IL-1b, IL17A (Th17), IL-22 (Th17)) (34), cardiovascular disease (ICAM-I, VCAM-I, hsCRP), co-morbidities (IL-6, VCAM-I, ICAM-I, sTNFR-II, and sTNFR-I), monocyte activation and microbial translocation (sCD14, sCD163, iFABP, D-dimer, LBP) (32), HIV disease progression (MCP1/CCL2, sCD14) and mortality (sCD14) in the context of HIV.…”
Section: Discussionsupporting
confidence: 93%
“…Elevation of sCD14, as observed in opioid users 19 an in our MET group, has been associated with microbial translocation. Levels of LBP, another translocation indicator which binds LPS, were significantly correlated to sCD14 levels (p = 0.0267), but was not detected as significantly different across our groups.…”
Section: Indicators Of Mucosal Integrity and Microbial Translocationsupporting
confidence: 61%
“…14 In vivo, the effect of opioids is thought to be mostly due to increased bacterial and/or fungal translocation resulting from a disruption of the intestinal homeostasis, via an altered mucosal barrier, 15 mucus secretion, 16 and/or bile acid metabolism. 17,18 Recent work 19 indicated that opioid use is associated with elevation of biomarkers of chronic inflammation, as well as markers of microbial translocation such as soluble (s) CD14, LPS-binding protein (LBP) and beta-D-glucan, independent of HIV infection. This is associated with the expression of activation markers CD38 and HLA-DR on T cells in both tissue and blood, T cell proliferation, and myeloid activation.…”
Section: Introductionmentioning
confidence: 99%
“…We observed zonulin levels in our study to be significantly higher compared to Ugandan and South African YPHIV [20,31,32]. Zonulin concentration was also higher when comparing to measurements performed in our laboratory in adults living with HIV [15,33], but similar to small cross-sectional studies in overweight and obese youth without HIV in the US and Europe [34–36]. Despite different methodologies used across studies, zonulin concentration being similar to overweight youth without HIV highlights that zonulin may play a role in the pathogenesis of metabolic disturbances in YPHIV in the Global North.…”
Section: Discussionsupporting
confidence: 70%